Hydrothermal carbonization of coffee husk: Optimization of experimental parameters and adsorption of methylene blue dye. Issue 5 (October 2017) - Ronix, Amanda; Pezoti, Osvaldo; Souza, Lucas S.; Souza, Isis P.A.F.; Bedin, Karen C.; Souza, Patrícia S.C.; Silva, Taís L.; Melo, Sandra A.R.; Cazetta, André L.; Almeida, Vitor C.
Graphical abstract: Highlights: Coffee husk was used as precursor of hydrochar. The experimental parameters were successfully optimized from RSM. Temperature and time were the significant effects. The optimized hydrochar (HCop ) exhibited well-developed surface area. HCop showed monolayer adsorption capacity of 34.85 mg g −1 for MB. Abstract: The coffee husk was used as precursor of hydrochar and chemometrics tools were applied to optimize the experimental conditions in order to obtain hydrochar with well-development surface area. The central composite rotatable design was employed and the optimization of parameters (temperature, time and water:precursor ratio) was performed from Response Surface Methodology (RSM). The analysis of variance showed that significant effects were: temperature and time. The optimal condition was found to be: temperature of 210 °C, time of 243 min, and water:precursor ratio of (3.4:1), resulting in a hydrochar (HCop ) with BET surface area value ( SBET ) of 31.3 m 2  g −1 . The HCop was properly characterized and applied in adsorption studies of methylene blue (MB) dye. The adsorption studies showed that the Elovich kinetic model and Langmuir isotherm model were that better described the experimental data. The monolayer adsorption maximum capacity of HCop was estimated to be 34.85 mg g −1 . Additionally, the thermodynamic study showed that adsorption occurs via spontaneous and endothermic process.